Leaders' core self-evaluation and team performance via serial mediation of relational identification and team potency - Sadia Arshad; Faisal Qadeer; Faisal Mahmood (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
Team performance has been the theme of scientific inquiry for a long time. However, researchers have recently diverted their attention to relational approaches to understanding highly congruent teams better. Unfolding the antecedents of team performance requires a nuanced display of leaders' traits like core self-evaluations (CSE), relational dynamics, and team beliefs in terms of potency to achieve performance excellence. The essence of congruence lies in how much the leader-follower relationship array complements each other in terms of leaders' trait-display as per expectations of the team members. So, the current study aims to substantiate the direction and magnitude of leaders' CSE influencing team performance via relational identification and team potency beliefs. A time-lagged data is collected from 400 employees' members and 80 immediate leaders working in a multinational bank from Pakistan. The obtained data is analyzed using SPSS and MPlus. Findings validated the indirect effects of leaders' CSE on team performance via relational identification and team potency path. The study endorsed the realization of team performance precisely through leaders' CSE, and leader-members relationship analogy that establishes relationship congruence elicits team potency and consequently augments team performance. Implications of the study and limitations and future directions are summarized for a thoughtful solicitation.
Keywords: 330; leaders’ core self-evaluation; relational identification; team potency; teamperformance; banking Sectors